2023
DOI: 10.3390/buildings14010010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Crack Width of HRB600 Grade High-Strength Steel Bar Reinforced Concrete Beams

Xiaoyi Hu,
Liang Zeng,
Hao Wu
et al.

Abstract: High-strength reinforcement is an important direction in the development of civil engineering. In order to fill the gap that the current concrete structure code GB50010 has no standard regulations applicable to HRB600-grade high-strength reinforcement, this paper conducted an experimental investigation on the crack width of eight concrete beams reinforced with HRB600-grade high-strength reinforcement. The study examined various parameters to understand the crack development process, crack spacing, and factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Liu [1] expounds the view that prefabricated buildings can effectively help realize the industrialization of construction projects and thus reduce the energy consumption of construction sites. In the past 10 years, the research on prefabricated concrete structures has been intensified, and much of the experimentation, modeling, and theoretical research has been done on precast concrete structure components (precast composite column) [2][3][4], material properties [5][6][7], structural vibration behaviors [8,9], node connections [10][11][12], construction method [13,14], or other points of prefabricated modular buildings. Ou [2] compared the seismic performance difference between an ultra-high-performance concrete (UHPC) prefabricated pipe concrete composite column and a conventional reinforced concrete column (RC column), and found that the stiffness, yield load, and ductility performance of the UHPC prefabricated composite column were better than those of the RC column in quasi-static tests.…”
Section: Introductionmentioning
confidence: 99%
“…Liu [1] expounds the view that prefabricated buildings can effectively help realize the industrialization of construction projects and thus reduce the energy consumption of construction sites. In the past 10 years, the research on prefabricated concrete structures has been intensified, and much of the experimentation, modeling, and theoretical research has been done on precast concrete structure components (precast composite column) [2][3][4], material properties [5][6][7], structural vibration behaviors [8,9], node connections [10][11][12], construction method [13,14], or other points of prefabricated modular buildings. Ou [2] compared the seismic performance difference between an ultra-high-performance concrete (UHPC) prefabricated pipe concrete composite column and a conventional reinforced concrete column (RC column), and found that the stiffness, yield load, and ductility performance of the UHPC prefabricated composite column were better than those of the RC column in quasi-static tests.…”
Section: Introductionmentioning
confidence: 99%